Implication of the Type III Effector RipS1 in the Cool-Virulence of Ralstonia solanacearum Strain UW551 - Schachterle, Jeffrey K.; Huang, Qi (Frontiers in Plant Science, 2021)
Members of the Ralstonia solanacearum species complex cause a variety of wilting diseases across a wide range of hosts by colonizing and blocking xylem vessels. Of great concern are race 3 biovar 2 strains of R. solanacearum capable of causing brown rot of potato at cool temperatures, which are select agents in the United States. To gain a better understanding of cool-virulence mechanisms, we generated libraries of transposon mutants in the cool-virulent strain R. solanacearum strain UW551 and screened 10,000 mutants using our seedling assay for significantly reduced virulence at 20oC. We found several mutants that exhibited reduced virulence at 28oC and 20oC, and also mutants that were only affected at the cooler temperature. One mutant of the latter chosen for further study had the transposon inserted in an intergenic region between a type III secretion system effector gene ripS1 and a major facilitator superfamily protein gene. Gene expression analysis showed that expression of ripS1 was altered by the transposon insertion, but not the major facilitator superfamily protein gene. An independent mutant with this insertion upstream of ripS1 was generated and used to confirm virulence and gene expression phenotypes. The effector, RipS1, has unknown function and is part of a family of effectors belonging to the largest known type III effectors. The functional connection between RipS1 and cool-virulence of R. solanacearum UW551 suggests that RipS1 (and/or its upstream promoter element) may serve as a potential target for development of cool-virulence-specific diagnostic tools to differentiate the highly regulated cool-virulent strains from non-cool-virulent strains of R. solanacearum. Our results provide important information for continued work toward a better understanding of cool-virulence of R. solanacearum and development of proper control strategies to combat this important plant pathogen.